'... And This Too Shall Pass!' Spiritual Striving and the Academic Life of Three Women - Lavia, Jennifer (Journal for the Study of Spirituality, 2011)
Spirituality and faith-based practices are central elements in the lives of Caribbean peoples. As academics from, or working in, the Caribbean whose practice pays attention to cultural origins, transformation, relevance and diversity, we have come to recognize the centrality and ‘taken-for-grantedness’ of faith and spirituality in our work. In this paper we examine our practice in light of three contexts: first, we explore how we have come to understand the role of faith and spirituality in our everyday lives; second, we discuss the ways in which spirituality and faith are deeply implicated in the curriculum we communicate with our students; and third, we examine the role of spirituality and faith in the process of doctoral supervision. We approach this paper as an exploratory set of narratives that struggle to articulate the opportunities and challenges of representing educational practice as both intellectual and spiritual pursuit. In doing so, we begin to understand how knowledge production is intimately linked with ‘uncovering and constructing truth as the fabric of everyday life’ (Dillard 2006: 20). We make problematic the silences and ambiguities of our practice which become manifest through our complicit and complex crafting of academic responses that are often sanitized for public consumption, silencing the spiritual through omission or sometimes transforming it into what might be considered more acceptable representations for the academic community.